Teachers’ readiness in using English in the teaching of mathematics and science / Sadai Jangoi - Jangoi, Sadai (2004)
This chapter will focus on the background of the elements in the study in order to brief the reader before proceeding to the process and finding of the research. Firstly, the researcher will discuss on the introduction part, which consists of the background of the study. Under the background ofthe study, the researcher will discuss on the importance of English in our country. This is followed by the brief history of issue that bring up the matter of Mathematics and Sciences English in Malaysia. Next, the researcher will focus on the current status of English in Malaysia and its implementation. Also the researcher will touch on the Statement of Problem, the Purpose of the Study, the Objectives of the Study, the Research Questions, the Limitation of the Study and finally the Definition of Terms.